Microscopic evaluation of the human dental pulp after full crown cementation with resin cement - Luiz C. Santiago; Luiz F. Pegoraro; Alberto Consolaro; Accácio L. do Valle; Gerson Bonfante (Brazilian Dental Science)
This study evaluated microscopically the dental pulp reactions in human premolars prepared for metaloceramic crowns cemented with different luting agents and also measured the remaining dentin thickness (RDT) of the prepared teeth. Twenty-five teeth were selected from patients that needed exodontia for orthodontic reasons and were randomly divided in three groups: group 1- five teeth were not prepared to serve as a positive control group; groups - 2, and 3 the teeth were prepared for metaloceramic crowns cemented with calcium-hydroxide cement (Life) and resin cement (Panavia Ex 21), respectively. After the final cementation, the teeth remaining in function for periods of seven and forty-five days and were extracted and prepared for microscopic analysis of pulp tissue and detection of presence of bacteria in the dentin tubules. The RDT were measured in 6 different regions of the prepared surface and presented a mean thickness ranging from 1.53 to 1.58 mm. The microscopic analysis did not show an inflammatory reaction of the pulp and bacteria were not found in the dentinal tubules. The resin cement evaluated in this study showed to be as biocompatible as calcium- hydroxide cement and therefore there should not be a clinical preoccupation regarding to pulp reaction.